Minimal Invasive Fixation Can Decrease Infection Rates in Diabetic and Obese Patients With Severe Ankle Fracture and Syndesmotic Injury. Issue 1 (February 2019) - Ebraheim, Nabil A.; Dailey, Matthew; Huff, Scott; Qu, Yihuai; White, Erik; Liu, Jiayong
Background. Ankle fractures involving syndesmosis disruption cause severely unstable joint conditions. Traditional invasive operations put certain patient groups at an increased risk of infection. There is limited literature discussing the outcomes of minimally invasive fixation of severe ankle fractures including syndesmotic injury, as clinicians may be tempted to treat these difficult cases with open reduction internal fixation (ORIF). Methods. A retrospective case-control study was conducted on patients treated at a level one trauma center. Patients were divided into 2 groups based on presence of diabetes and/or obesity (body mass index ≥30.0 kg/m 2 ). Those with either comorbidity were defined as high infection risk patients and placed in a comorbidity group. Patients were further divided into subgroups based on the operation's invasiveness; either traditional ORIF or percutaneous cannulated screw fixation. Results. Comorbid patients (N = 67) were more likely to sustain Weber C fractures compared to noncomorbid patients (N = 43) (59.70% to 37.21%, P = .019). Additionally, patients receiving minimally invasive fixation procedures experienced fewer infections than those receiving ORIF (0 vs 11 incidences, P = .01), without effect on union rates, fracture reduction, pain, need for revision surgery, or time to full weightbearing. Conclusions: Diabetic and obese patients are at an increased risk of experiencing severe ankle fractures. The use of minimally invasive fixation methods can reduce the risk of postoperative infection without sacrificing other surgical outcomes, even with fractures involving syndesmotic injury. Levels of Evidence: Therapeutic, Level III: Retrospective comparative study